„Jesteśmy tu dla Polski”. III Rada Narodowa RP wobec wydarzeń w kraju (1949–1951) - Tarka, Krzysztof (Czasopismo Prawno-Historyczne, 2018)
The article presents discussions on the situation in Poland which took place at the forum of the Third National Council. The Council was appointed by the president of Poland in Exile August Zaleski in 1949. It was vicariously performing some of the functions of the Parliament and as such it was an advisory body to the president and to the government. Its term of office lasted for two years (between 1949 and 1951). Polish authorities in exile regarded Poland as an occupied country and that it was ruled by imposed agents. News coming from the country indicated that the communists ruling in Poland were steering it toward its total sovietisation. Politicians in emigration appealed numerous times to their fellow countrymen in the homeland not to undertake armed combat. They feared that an anti-communist uprising would end in disaster. Their goal was free Poland, independent and whole. However, they could not create a programme which would enable achieving this goal.